Outdoor mobile broadband access with 802.11. - Alexander, Paul; Haley, David; Alexander, Paul.
The IEEE 802.11 OFDM physical layer was designed primarily for indoor local area networks. Commercially available 802.11 radios suffer greatly reduced performance, even failing completely, when deployed outdoors, where long delay spreads cause self-interference, and vehicular mobility causes fast variations in the radio channel parameters. This article describes an advanced OFDM receiver that overcomes these problems. It works by combining all useful received energy, accounting for inter-symbol interference, and accurately tracking radio channel variations. Complexity and performance advantages arc gained by splitting the processing between the time and frequency domains. Computer simulations show that even for outdoor urban environments at speeds greater than 140 mph, this receiver delivers performance comparable to a non-mobile, indoor system.
Keywords: IEEE 802.11 OFDM physical layer; OFDM receiver; Indoor local area networks; Radio channel variations